The Relationship Between Different Variables For Math Literacy In PISA 2012: A Hybrid Model Study PISA 2012’de Matematik Okuryazarlığına Ait Farklı Değişkenler Arasındaki İlişki: Bir Hibrid Model Çalışması - Sami Pektaş; Mustafa Kılınç (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
In this study, it is aimed to determine the relationship between math self-efficacy sense, math interest, math work ethics and math achievement of students taking part in PISA 2012 Turkey sample. The data including 3211 students taking part in PISA 2012 Turkey sample have been utilized. When we look at the established hybrid model, math self-efficacy sense, math interest and math work ethics explain %64 of math achievement. Self-efficacy sense and math work ethics explain %64 of math achievement. Math self-efficacy sense and math interest explain %54 of math achievement. In general, it is seen that math self-efficacy senses of students explain math achievement in a low level. Besides, it is concluded that math achievement has been explained in a high level in this hybrid model established by taking math interest and work ethics.